Synergy of oxalic acid and sunlight triggered Cr(III)-bearing Schwertmannite transformation: Reaction mechanism, Cr and C spatial distribution and speciation on the nano scale. (15th July 2022) - Yao, Qian; Guo, Chuling; Li, Xiaofei; Jin, Xiaohu; Lu, Guining; Yi, Xiaoyun; Huang, Weilin; Dang, Zhi
Abstract: Cr(III)-bearing iron minerals are widely present in acid mine drainage (AMD)-contaminated areas. In the light-transmitting layer of natural systems, dissolved organic matter (DOM) can synergize with solar irradiation to transform Fe-bearing minerals, but the behavior of Cr(III) and its interfacial reaction with schwertmannite (Sch) under the combined effect of DOM and solar radiation remain unclear. Oxalic acid (OA) was selected as a form of DOM to investigate its combined effect with solar radiation on substituted-Cr(III) schwertmannite (Cr-Sch) under acidic conditions (pH = 3). Batch photoaging experiments in combination with in situ attenuated total reflectance-Fourier transform infrared spectrometry (ATR-FTIR), aberration-corrected scanning transmission electron microscopy (Cs-STEM), ultra-performance liquid chromatography-quadrupole-orbitrap mass spectrometry (UPLC-Q-Orbitrap MS), were employed to investigate Cr-Sch photoreductive dissolution process and elemental distribution. With increasing OA concentrations, Sch transformed to different second minerals: goethite and humboldtine under 1 mM and 5 mM oxalate condition, respectively. Photoreductive dissolution processes occur both on the surface of the minerals and in solution. Ligand-to-metal charge transfer (LMCT) is the dominant pathway of Sch photoreduction in solution when oxygen is absent, and it also occurs with superoxide mediated iron reduction (SMIR) under the aerobic conditions. With increasing OA concentrations, the conversion rate of Sch increases (the ratio of humboldtine to goethite increases), and the proportion of extractable Cr and solid-associated C increases. The findings reveal that OA plays a significant role in controlling the cycling of Fe/C and heavy metal elements under sunlight in the AMD-contaminated environment.